Development of Rooftop Solar Power Plant (PLTS) on Parking Areas for EV Charging Station at Sumsel-8 Mine Mouth Power Plant - Rendy Anggara, Gusti; Silviana; Yoyo Wardana, Asep (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
The PLTU MT Sumsel-8, a coal-based power plant, has significant potential to implement renewable energy solutions to enhance energy efficiency and operational sustainability. One viable solution is the construction of a rooftop solar power plant (PLTS) in the parking area with an off-grid system. This system is designed with a capacity of 162 kWp to meet the electricity needs of supporting facilities at the power plant, such as lighting, cooling systems, and office operations. In addition to generating clean energy, the installation of solar panels on the parking lot roof also provides additional benefits, including vehicle protection from solar heat and the optimization of previously underutilized land. However, before implementing this system, a comprehensive feasibility study is required, encompassing technical, economic, and environmental evaluations. Simulation results using Helioscope software indicate that the proposed PLTS system with the stated capacity can generate 225.413,2 kWh of energy per year. Considering the energy storage capacity of electric vehicles, the simulation results suggest that the energy production can provide enough charging capacity for 7 to 8 vehicles per day for vehicles with battery capacity 77 to 82,5 kWh and up to 23 vehicles per day for smaller capacity battery which is 26,7 kWh. This study is expected to offer recommendations for the implementation of rooftop PLTS at PLTU and contribute to the strategy for sustainable energy options in Indonesia.